2008
DOI: 10.1002/sia.2743
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of interface impurities in electroplated Cu layers by using GD‐OES and TOF‐SIMS

Abstract: Electrochemically deposited (ECD) copper layers used as interconnect metallizations exhibit incorporated impurities in the form of H, S, C, O, N, and Cl originating from additives in the electrolyte solution. These impurities were observed in the whole layer and especially at the interface to the underlying Cu seed layer due to an increased adsorption at the beginning of the electroplating process. Time-of-flight (TOF)-SIMS and glow discharge optical emission spectroscopy (GD-OES) were carried out for interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…In terms of lead-free material research, it was Laurila et al 59 whom first found detectable amounts of impurities in electrochemically deposited Cu for UBM, and found a direct link between the "purity" of the Cu used and void formation. Since then, there has been a large number of publications 61,62,72,73,[90][91][92] [II], [IV], [V] that have researched the link between electroplating parameters, residual impurities and void formation. A particular focus has been on the decomposition and incorporation of additives into the deposited film during Cu electroplating.…”
Section: Trace Impuritiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of lead-free material research, it was Laurila et al 59 whom first found detectable amounts of impurities in electrochemically deposited Cu for UBM, and found a direct link between the "purity" of the Cu used and void formation. Since then, there has been a large number of publications 61,62,72,73,[90][91][92] [II], [IV], [V] that have researched the link between electroplating parameters, residual impurities and void formation. A particular focus has been on the decomposition and incorporation of additives into the deposited film during Cu electroplating.…”
Section: Trace Impuritiesmentioning
confidence: 99%
“…Liu et al speculated that the higher current density results in a shorter deposition time that allows less time for the additives to desorb from the cathode surface. Klemm et al 91 undertook a study that examined the impact of two different electroplating modes on the impurity incorporation as a function of depth from the Cu surface. The two modes are normal and hot plating.…”
Section: Trace Impuritiesmentioning
confidence: 99%
“…They also examined the corrosion and heterogeneity of American native copper by SEM-EDX and EPMA. Impurities (H, S, C, O, N, and Cl) were observed in electrochemically deposited copper thin films by ToF-SIMS and GD-MS as reported by Klemm et al 38 The advantages and disadvantages of these techniques for thin film analyses were discussed in the paper but not described in the abstract. The oxidation of silver by gaseous S 2À and S 4+ species was studied using atomic force microscopy, in-situ micro-balance and ToF-SIMS, as reported by Kleber et al 39 The authors noted that the sulfidation process strongly depends on the relative humidity content and the oxygen in the ambient atmosphere.…”
Section: Non-ferrous Metals and Alloysmentioning
confidence: 91%
“…This can be realised through minimising contaminants from the carrier gas and from the specimen and anode surfaces. 6 It is well known that the carrier gas purity is one of the most critical parameters for reliable GD analysis; but even if the partial pressure of contaminants in the gas is very low, a monolayer of impurities is formed within a very short time (at argon pressures of 10 mbar, a monolayer is formed within 500 ns assuming a sticking probability of 1 and using kinetic theory of gases with Maxwellian velocity distribution and perfect gas law).…”
mentioning
confidence: 99%
“…The use of monocrystalline silicon as the sacrificial specimen may be effective. 9 However, careful selection of the sacrificial specimen is important to avoid distortion of the depth profile, since the sacrificial material may be removed from the inner walls of the anode during depth profiling. This approach is an excellent alternative to cleaning the discharge chamber using solvents and other chemicals that, generally, are not completely removed from the surface and often leave surface residues.…”
mentioning
confidence: 99%